PENERAPAN METODE INQUIRY UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS V SDN 4 KALIMAS KECAMATAN TELUK BATANG - Nurilla, Nurilla (Universitas Tanjungpura, 2020)
Science subject is one of the curricular fields of study at the Elementary School (SD) level. Due to the low understanding of students towards this subject, especially the application of the inquiry method to improve student learning outcomes in class V SD Negeri 4 Kalimas, the writer makes improvements to learning. This study aims to improve students’ learning outcomes and activitiesin science subjects using the inquiry method application material. After carrying out the teaching and learning activities using the inquiry method, student learning outcomes and activities have increased. This was shown from the data collected, that in the pre-cycle learning activities there are only 7 students who got a score ≥ minimun standard achievement with a class average scoreof 41.5. So the description of the data collected can be concluded that the use of the inquiry method can improve students’ learning outcomes and activities in science subjects of class V SD Negeri 4 Kalimas. Thus, the inquiry method is one of the effective learning methods in improving students’ learning outcomes and activities in science subjects.